Pengaruh Penggunaan Aplikasi Quizizz Terhadap Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti di Kelas VII SMP Negeri 3 Bahorok - Siti Fatimah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The integration of technology in education has become essential, particularly in enhancing student engagement and learning outcomes. This study aimed to evaluate the impact of the Quizizz application on students' learning results in Islamic Education and Character Education at SMP Negeri 3 Bahorok. Employing a quantitative approach with a descriptive design, the research involved 22 students, utilizing questionnaires, observations, and documentation to collect data. The findings revealed a significant improvement in students' average test scores, rising from 65 to 85 after six weeks of implementing Quizizz, indicating its effectiveness in enhancing understanding and retention of material. Additionally, 82% of students achieved the Minimum Completeness Criteria (KKM) post-implementation, compared to only 50% before. These results suggest that Quizizz significantly boosts student motivation and participation in learning